Sonographic Evaluation of Diaphragmatic Dysfunction: Technique, Interpretation, and Clinical Applications. Issue 6 (November 2019) - Dass, Chandra; Dako, Farouk; Simpson, Scott; Marchetti, Nathaniel; Steiner, Robert; Criner, Gerard
Abstract : Diaphragmatic dysfunction is a potential cause of dyspnea that can lead to significant morbidity. The purpose of this review article is to provide readers with the essentials for performing diaphragm ultrasonography, image interpretation, and the technical limitations one needs to be aware of. Diaphragm ultrasonography is simple to perform and has proven to be an accurate and safe bedside modality, overcoming many of the traditional limitations of fluoroscopy.